Inhibition of Ubiquitin-Specific Proteases as a Novel Anticancer Therapeutic Strategy - Yuan, Tao; Yan, Fangjie; Ying, Meidan; Cao, Ji; He, Qiaojun; Zhu, Hong; Yang, Bo (Frontiers in Pharmacology, 2018)
Dysfunction or dysregulation of the ubiquitin proteasome system (UPS) is closely related to tumourigenesis and the development of multiple cancers. Targeting the UPS provides a new anticancer therapeutic strategy, but clinically available UPS-targeted inhibitors, including lenalidomide and bortezomib, are limited to treat solid tumours. Under physiological conditions, deubiquitinases or deubiquitinating enzymes (DUBs) play vital roles in the UPS by removing ubiquitin from substrate proteins and regulating their proteasomal degradation and sub-localization, thus maintaining the balance between ubiquitination and deubiquitination for protein quality control and homeostasis. The aberrant expression or function of DUBs generally leads to the occurrence and progression of a series of disorders, including malignant tumours. Therefore, targeting DUBs is a novel anticancer therapeutic strategy. Ubiquitin-specific proteases (USPs) are the largest subfamily of DUBs which have attracted considerable interest as anticancer targets. Most of USPs are abnormally activated or expressed in a variety of malignant tumours or in the tumour microenvironment, making them ideal anticancer target candidates, which indicates that USPs inhibitors may be a class of potential anticancer therapeutic agents. However, there are no relevant inhibitors targeting USPs have entered clinical trial so far. In this review, we will summarize the roles and mechanisms of USPs in malignant transformation and progression as well as recent advances of small-molecule inhibitors targeting USPs.